Now you can plagiarise anything from the Net - Abd Razak, Dzulkifli (2006)
ACADEME, it seems, is not what it used to be, with even Russian President Vladimir Putin being dragged into the controversy. This column last month talked about the scandal in the stem cell research in Korea as well as other highprofile cases in Japan and Norway which seem to indicate that there is something unusual in how the research was conducted. Perhaps these could have been just isolated cases where individuals were, according to the oncefamed Dr Hwang Woosuk of South Korea, in defending his action, "blinded by work and the drive for ambition". Unfortunately, the recent spate of events seems to suggest that these were in fact the tip of a larger iceberg of academic scandals. The latest revelation was in China when a report was made at the recent meeting of the top advisory body of the Chinese People’s Political Consultative Conference.